Robotic exploration beneath the ice : the challenges, risks and rewards of deploying an autonomous underwater vehicle in Antarctica - King, PD (Papers and Proceedings of The Royal Society of Tasmania, 2021)
Measurements beneath Antarctic ice shelves are critical to our understanding of how the glaciers will change and melt. To access these regions, we rely on autonomous underwater vehicles (AUV), which are free-swimming robots. The Australian Maritime College in Launceston, Tasmania, is leading efforts to deploy these vehicles in some of the harshest environments on Earth. This paper provides an overview of the history and recent Australian efforts in deploying AUVs in under-ice environments and discusses recent advances in mission planning and the ongoing challenges to take measurements from beneath ice shelves.